Effect of season and supplementation on the utilization of natural herbage by grazing calves in the wet-intermediate zone of Sri Lanka - T. Seresinhe; K.K. Pathirana (Italian Journal of Animal Science, 2010)
A grazing experiment was conducted to determine the production potential of buffaloes as a function of supplementation and pasture production during different seasons. Six groups of two cross-bred Murrah buffalo heifers of 16 ± 3 months of age mean live weight of 127 ± 10 kg were randomized into 0.6ha of coconut land to remain and continuously graze the herbage from Jan 2004 to Jan 2005. The treatments were: (T1) Natural herbage; (T2) T1+ supplement (rice bran/molasses/urea/mineral mixture) + Gliricia sepium (3-5kg / day). Dry matter (DM) yields were not only influenced by the seasons, but were also related linearly to the seasonal rainfall. The DM yield and CP content increased towards the end of the experiment in T2 as compared to T1. The average daily gain and total gain of both treatments were linearly related to the DM yield and ranged from 297 kg/head/ha for T1 and 446 kg /head/ ha for T2. It is concluded that season had a significant influence on ruminant production under natural grazing conditions. Supplementation could compensate the seasonal fluctuations in grazed herbage.